Use of an emollient‐containing diaper and pH‐buffered wipe regimen restores skin pH and reduces residual enzymatic activity. Issue 4 (21st April 2020) - Gustin, Jennifer; Bohman, Lisa; Ogle, Julie; Chaudhary, Tanuja; Li, Lijuan; Fadayel, Gina; Mitchell, Maria C.; Narendran, Vivek; Visscher, Marty O.; Carr, Andrew N.
Abstract: Background/Objectives: Diaper dermatitis is one of the most frequent skin conditions affecting infants and is associated with elevated skin pH, exposure to urine and feces, and increased fecal protease and lipase activity, resulting in stratum corneum barrier damage and increased risk of infection. The study aim was to determine the impact of two diaper and wipe regimens on newborn infant skin pH and residual enzyme activity after stool cleaning. Methods: Two diaper and wipe regimens were compared in a randomized, single‐blinded crossover study. Regimen A paired an emollient‐containing diaper with an acidic, pH‐buffered wipe. Regimen B was a non‐emollient diaper and wipe with limited buffering capacity. A 3‐day washout period preceded each 3‐day regimen use period. Skin pH at the perianal/buttocks interface (PBI), genital region, and undiapered chest control were measured at baseline and day 3. Skin swabs were collected for residual enzyme activity after a stool cleaning event. Results: Diapered skin pH at the PBI was similar to undiapered skin after 3 days of use for Regimen A, while PBI pH for Regimen B was elevated versus control. PBI pH was lower for Regimen A versus Regimen B. After a stool cleaning, PBI skin pH for Regimen A was lower immediately and had lower residual enzyme activity versus Regimen B ( P  < .05), and the pH‐lowering effect was sustained up to 60 minutes. Conclusions: These results suggest that the use of an emollient‐containing diaper with a pH‐buffered wipe creates conditions favorable to optimum diapered skin health.